LEARNING STRATEGY: IDENTIFYING STRATEGY USED BY LANGUAGE LEARNERS (FOR TOEFL, IELTS, AND GLOBAL ENGLISH LEARNERS) - Dara Fitria Munzaki (Jurnal Ilmiah Didaktika, 2018)
English proficiency test is the most widely taken for many purposes. Most of people take TOEFL, IELTS, and global English as learning fields to achieve their learning purposes. However the score for these proficiency tests are low. Consequently, they need to find solution to increase the score, for instance using learning strategies. There are several language strategies can be used to help them to achieve it. This study focuses on identifying which strategies used by language learners for learning IELTS, TOEFL, and global English and the frequency of using the strategies. The study proposes two research questions, first, what are strategies mostly used by the language learners in learning IELTS, TOEFL, and global English? Second, how often do the learning strategies used by the learners? The study is conducted in descriptive statistics, collected the data through SILL questionnaires consist of 35 statements, and includes 27 respondents from Bandung, West Java. This study found that learners used the learning strategies to help them in learning language proficiency, however they used it instability and inconsistency. Overall, to achieve the learning purposes, learners are suggested to trigger themselves to use learning strategies in consistent and regularly.